2013
DOI: 10.1038/sc.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in Korean persons with spinal cord injury

Abstract: Study design: Cross-sectional survey. Objectives: To investigate the prevalence of suicidal ideation and attempt in Korean persons with spinal cord injury (SCI) and the factors related with suicidal ideation in comparison with a control group (CG). Settings: Community-dwelling persons with chronic SCI in Korea. Methods: A total of 382 persons with chronic SCI and 1104 able-bodied persons randomly selected from the general population and matched for age, sex and education level were compared. Suicidal ideation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…19 In addition, one study reported no difference between differing levels of injury. 24 It is therefore not possible to draw an accurate conclusion from these findings. However, one suggestion is that isolation may have a role in increasing the risk of suicidal behaviour.…”
Section: Summary Of Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…19 In addition, one study reported no difference between differing levels of injury. 24 It is therefore not possible to draw an accurate conclusion from these findings. However, one suggestion is that isolation may have a role in increasing the risk of suicidal behaviour.…”
Section: Summary Of Findingsmentioning
confidence: 96%
“…18,24 In the study by Hagen et al, 18 cause-specific standardised mortality rate for suicide was 3.7 in males and 37.6 in females. Nam et al 24 reported female gender to be a significant risk factor for suicidal ideation, with an odds ratio of 3.7. However, interestingly, in one study, all those who committed suicide were male.…”
Section: Gendermentioning
confidence: 97%
See 1 more Smart Citation
“…Understanding suicidality in the SCI population is of utmost importance, as individuals with SCI reportedly have more than a three-fold higher suicide incidence than those without SCI [ 3 , 4 ]. It has also been observed that 34.8% of individuals with chronic SCI experience suicidal ideation, with 17.3% having attempted suicide and a maximum of 11% resulting in fatalities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 In addition to experiencing significant physiological concerns and impairments to everyday functioning, individuals with SCI are also at increased risk of experiencing psychological distress, including increased depression, anxiety, post-traumatic stress disorder, and social isolation, which may contribute to higher rates of suicidal ideation (SI) in individuals with SCI compared with the general population. 10 , 11 , 12 , 13 , 14 , 15 , 16 Indeed, research suggests that the experience of SI is significantly more common among persons with SCI, with an estimated 13.3% prevalence of SI within 2 weeks of screening, than among individuals of the general US population, who have an estimated annual prevalence of 3.7%. 10 , 17 , 18…”
mentioning
confidence: 99%